Risk of malignancy index 4 in preoperative evaluation of patients with ovarian tumours - Singhal, Sunita; Rajoria, Lata; Mital, Premlata; Batar, Alka; Ainani, Richa; Agarwal, Monika; ., Urmila; Chaudhary, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian tumors usually presents as adnexal masses which may be benign or malignant. Accurate and timely diagnosis of an adnexal mass is a challenge for the gynecologists. Currently clinical examination, ultrasonographic assessment and ovarian tumour markers (CA 125, beta hCG, AFP, LDH) are routinely done at our centre to evaluate patients with ovarian tumours. The study was designed to evaluate the ability of RMI 4 to discriminate benign ovarian tumor from malignant ovarian tumor in patients attending Department of Obstetrics and Gynaecology, S.M.S. Medical College, Jaipur. Methods: 200 patients diagnosed to have ovarian tumours were included in the study after obtaining written consent. Ultrasonographic characteristic, menopausal status and serum CA 125 levels were documented preoperatively. Risk of malignancy index 4 was calculated and correlated with histopathological diagnosis. Results: At a cut-off point of 450, RMI 4 had a sensitivity of 67.5% (95% CI: 50.87-81.43%), specificity of 98.75% (95.56-99.85%), positive likelyhood ratio of 54, negative likelyhood ratio of 0.33, a positive predictive value of 93.1%, negative predictive value of 92.4% and diagnostic accuracy of 92.5%. Conclusions: RMI 4 is a simple, cost effective, reliable scoring system that is easily applicable method in primary evaluation of patients with ovarian tumours with a sensitivity of 67.5% and specificity of 98.75%.